Nilai Sosial Dalam Tradisi Pacu Jalur Di Gunung Toar Kabupaten Kuantan Singingi - Kamilah, Intan Putri; Rizkya, Nindya Destri Nur; Fatimah, Siti; Marhadi, Hendri (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
The Pacu Jalur tradition in Gunung Toar, Kuantan Singingi Regency, is an intangible cultural heritage rich in social values such as mutual cooperation, deliberation, solidarity, sportsmanship, and communal loyalty. This study employs a descriptive qualitative approach through interviews and participatory observation to explore the social meaning embedded in each stage of the Pacu Jalur tradition, from boat preparation to race execution. The findings reveal that this tradition serves not only as a cultural spectacle but also as a character education platform and a medium for preserving cultural identity. The active intergenerational community involvement, along with governmental support, highlights Pacu Jalur's potential as a model for culturally grounded social education that adapts to contemporary societal dynamics.